2020
DOI: 10.1186/s12974-020-01890-6
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor kappa B activation appears weaker in schizophrenia patients with high brain cytokines than in non-schizophrenic controls with high brain cytokines

Abstract: Background: High inflammation status despite an absence of known infection characterizes a subpopulation of people with schizophrenia who suffer from more severe cognitive deficits, less cortical grey matter, and worse neuropathology. Transcripts encoding factors upstream of nuclear factor kappa B (NF-κB), a major transcriptional activator for the synthesis of pro-inflammatory cytokines, are increased in the frontal cortex in schizophrenia compared to controls. However, the extent to which these changes are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 64 publications
1
19
1
Order By: Relevance
“…HIVEP2 and FOXP1 code for transcription factors and both have previously been related to autism [34][35][36]. HIVEP2 has also been linked to schizophrenia and substance use disorders [37][38][39], and knockout mice for this gene show hyperactivity, anxiety, and schizophrenia-related behaviors [40,41], which is in line with the associations we found between ADHD and anxiety. FOXP1 was also found to be associated with aggression in our study, but, to our knowledge, it has not been previously related to aggressive behavior.…”
Section: Discussionsupporting
confidence: 89%
“…HIVEP2 and FOXP1 code for transcription factors and both have previously been related to autism [34][35][36]. HIVEP2 has also been linked to schizophrenia and substance use disorders [37][38][39], and knockout mice for this gene show hyperactivity, anxiety, and schizophrenia-related behaviors [40,41], which is in line with the associations we found between ADHD and anxiety. FOXP1 was also found to be associated with aggression in our study, but, to our knowledge, it has not been previously related to aggressive behavior.…”
Section: Discussionsupporting
confidence: 89%
“…Given that NF-κB kinases are necessary for forward propagation of the NF-κB signal from receptor to nucleus [ 72 ], it may appear counterintuitive that a subset of people with schizophrenia had downregulated peripheral expression of IKKβ and NIK transcripts but increased expression of IL-1β mRNA and CRP. This is in contrast to the brain, where we found the expected strong, positive relationship between NF-κB kinase mRNAs and proinflammatory cytokine mRNAs overall [ 14 ]. Our results here suggest that synthesizing less IKKβ and NIK mRNA may potentiate, not dampen, inflammation in the periphery in people with schizophrenia.…”
Section: Discussioncontrasting
confidence: 57%
“…Further, several whole-genome and RNA-sequencing studies have found changes in the immune system of patients in the brain and blood [ 8 10 ], though few studies have identified specific aspects of immunoregulatory pathways that may be causing such aberrations. While it is not currently known what drives this presumed noninfective inflammation in schizophrenia, overactivity of the immune regulator nuclear factor kappa B (NF-κB) has recently been proposed to prime patients for exaggerated and prolonged immune responses in the brain [ 3 , 11 14 ]. Consistent with this, we and others have found altered expression of NF-κB pathway mRNAs in the post-mortem cerebral cortex of people with schizophrenia [ 12 , 14 ], and we showed that individuals with increased levels of NF-κB-inducing mRNAs also have increased levels of pro-inflammatory cytokine transcripts in the brain (for a detailed explanation of NF-κB-signaling pathways, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…With our cohort of long-term, treatment-resistant SZ patients [ 56 ], high IL-6 was detected only in individual patients and was associated with impaired antigen presentation and intermediately activated monocytes. Murphy and colleagues also described a paradox state of weaker NF-κB activation in SZ patients, yet with high pro-inflammatory cytokine concentrations in the brain [ 57 ]. Corsi-Zuelli and Deakin hypothesized this “microglia paradox” to be, in part, caused by dysregulated T reg cells in the brain [ 58 ].…”
Section: Discussionmentioning
confidence: 99%